Polish Political Emigrants in the Visual Propaganda of the People’s Republic of Poland - Białecki, Konrad (Sensus Historiae, 2025)
In the first years after the Second World War, one of the groups particularly fought against by the communist authorities were the representatives of the Polish government in exile. The vast majority of them, not wanting to return to a Poland ruled by communists subordinate to the Soviet Union, remained in the UK. One of the tools of the fight against political émigrés was visual propaganda. During the Stalinist period, Poles remaining in London were portrayed as traitors, collaborating with the Nazis from Germany and the imperialists from the United States. In subsequent decades, this image became more nuanced. This was especially true of the so-called ordinary émigrés who had no social or political function. In contrast, representatives of the Polish government in exile were subjected to damnatio memoriae.